Biotechnological progresses in modelling the human endometrium: the evolution of current in vitro techniques and emerging trends - Marcos Agustina-Hernández; Emilio Francés-Herrero; María Gómez-Álvarez; Paula Alonso-Frías; Mónica Romeu; Ana Monzó; Hortensia Ferrero; Clara Bueno-Fernandez; Clara Bueno-Fernandez; Irene Cervelló (Frontiers in Bioengineering and Biotechnology)
The endometrium plays a fundamental role in the reproductive system yet many etiologies of infertility-related endometrial diseases such as endometriosis, adenomyosis, Asherman’s syndrome or endometrial cancer remain unknown. There are currently no treatments that minimize the effects of this devastating disorder. Appropriate model systems that closely mimic the architecture and function of the endometrium in healthy and pathological states are needed to understand the underlying molecular pathways and develop novel or more effective treatments. This review summarizes the key milestones of in vitro culture models of the human endometrium throughout history, as well as the applications of advanced bioengineering techniques in the modelling of both healthy and pathological endometrium. Opportunities for future approaches are also discussed.